Online auction system : developing an auction information system for Sejahtera properties auctioneers / Norhidayat Kamarudin - Kamarudin, Norhidayat (Faculty of Computer and Mathematical Sciences, 2007)
Property auction information is very important components for the property auctioneers company management and the way of managing it is also important. The main purpose of this research paper is to assist company's staff to run daily business activities through an information system. This research focused on the development of online auction system in order to gain competitive advantages and improve the effectiveness of the processes within the company. The features that also has been included into this system that make it difference with others is by merging the system with GIS application to make user easy to find the location for each property for auction in the system. This application is developed using the open source software which is Apache Web Server, MySQL Database, phpMyAdmin Database Administrator plus with PHP programming language and also Google Map API. The problem occurs with the current manually technique within the company is difficulty to find the record that will lead to a poor information management and need a lot of time and energy. Therefore, this application will reduce this problem and make the company processes faster than before.